The story of Edgar Sawtelle : a novel - Wroblewski, David (Ecco, 2008)
A tale reminiscent of "Hamlet" that also celebrates the alliance between humans and dogs follows speech-disabled Wisconsin youth Edgar, who bonds with three yearling canines and struggles to prove that his sinister uncle is responsible for his father's death.